2018
DOI: 10.1007/s10886-018-0931-7
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Bioassays and Field Evaluation of Hydroxycoumarins and their Alkyl Derivatives as Repellents or Kairomones for Aedes albopictus Skuse (Diptera: Culicidae)

Abstract: In recent years, a significant increase in mosquito-borne diseases has been recorded worldwide. Faced with the limitations of existing methods for controlling the vector mosquito population, the development of attractants to bait traps and repellents to limit host-vector contacts could be promising and environmentally-friendly control strategies. The purpose of this study was to evaluate the effect of hydroxycoumarins and their alkyls derivatives against Aedes albopictus, the main vector of several arboviruses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…A synergistic effect was observed for the blend 4-hydroxycoumarin (10 mg) and octenol (2 mg) in this experiment. We reported similar results with Aedes using the sentinel-type trap 20 . It seems that it is 4-hydroxycoumarin that plays a major role in synergy because even without octenol the selectivity remains high compared to other products.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…A synergistic effect was observed for the blend 4-hydroxycoumarin (10 mg) and octenol (2 mg) in this experiment. We reported similar results with Aedes using the sentinel-type trap 20 . It seems that it is 4-hydroxycoumarin that plays a major role in synergy because even without octenol the selectivity remains high compared to other products.…”
Section: Discussionsupporting
confidence: 79%
“…laboratory and field assays 20 . Preliminary field tests in the east of Madagascar, using CDC light traps, have shown that the same compound also attracts Anopheles mosquito species.…”
mentioning
confidence: 99%
“…Fay [56], the Fay-Prince trap [57], the black cylinder suction trap [58], duplex cone trap [59]) and lure-based traps. For the latter, artificial odours and attractants have been developed and tested for use in traps such as kairomone blends [60][61][62][63][64][65][66][67], BG-Lure® cartridges [68][69][70], and carbon dioxide (CO2) 6 [71]. Additionally other trapping methods have been developed that use live hosts as lures (e.g.…”
mentioning
confidence: 99%
“…This test allows to determine the overall deviation from the expected proportion (50:50 in our case) and whether there is significant variation among the repeated trials (McDonald, 2014). For each assay, the KI was also calculated to assess the relative attractiveness of the different bacterial strains (Andrianjafy et al, 2018). This index represents the percentage of the difference between the number of mosquitoes in the compartment containing the tested isolate (P) and in the control (sterile LBm medium) (T) divided by the sum of mosquitoes in both compartments (P + T).…”
Section: Growth Curvesmentioning
confidence: 99%